2022
DOI: 10.1007/s10508-021-02153-y
|View full text |Cite
|
Sign up to set email alerts
|

Single and Partnered Individuals’ Sexual Satisfaction as a Function of Sexual Desire and Activities: Results Using a Sexual Satisfaction Scale Demonstrating Measurement Invariance Across Partnership Status

Abstract: Although some evidence exists to suggest that single (i.e., unpartnered) individuals are less sexually satisfied on average than are partnered individuals, it is unclear whether the variables correlating with each group’s sexual satisfaction are similar or different. This research sought to examine how desire for and actual engagement in solitary and partnered sexual activities are associated with both groups’ sexual satisfaction. We first conducted a preliminary study ( n = 572) to test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 79 publications
1
28
0
Order By: Relevance
“…Furthermore, among the 32 factors related with SS assessed, those rated as more likely to affect these women’s satisfaction were those directly related with relationships (i.e., attraction to, and confidence with the sexual partner or the absence of a feeling of obligation to do something unwanted). These results are consistent with previous findings [ 21 , 53 ], since sexuality is mostly considered as a shared function that is undoubtedly related to confidence, emotion, attraction and other partner-related factors, and has commonly been studied within romantic relationships [ 54 ]. It is important to highlight that the feeling of obligation to have a sexual relationship or the belief that a woman has to accept or be receptive to the partner’s sexual approaches (sex-for-obligation, still a common motivation/drive for sex for women in heterosexual relationships) have been reported to predict lower SS [ 55 ], hence the importance of assessing these factors to collect data to plan educative or therapeutic interventions and research designs.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, among the 32 factors related with SS assessed, those rated as more likely to affect these women’s satisfaction were those directly related with relationships (i.e., attraction to, and confidence with the sexual partner or the absence of a feeling of obligation to do something unwanted). These results are consistent with previous findings [ 21 , 53 ], since sexuality is mostly considered as a shared function that is undoubtedly related to confidence, emotion, attraction and other partner-related factors, and has commonly been studied within romantic relationships [ 54 ]. It is important to highlight that the feeling of obligation to have a sexual relationship or the belief that a woman has to accept or be receptive to the partner’s sexual approaches (sex-for-obligation, still a common motivation/drive for sex for women in heterosexual relationships) have been reported to predict lower SS [ 55 ], hence the importance of assessing these factors to collect data to plan educative or therapeutic interventions and research designs.…”
Section: Discussionsupporting
confidence: 93%
“…Thus, future research would do well to examine the extent to which the effects found in the current research are accounted for by attachment security specifically as opposed to personality traits such as agreeableness and neuroticism. In addition, although our study focuses on single individuals in order to address the lack of descriptive, within‐group data for singles, without a comparison group of individuals in relationships we cannot and do not claim that our results are unique to those who are single (see Park & MacDonald, in press, for an example of singlehood dynamics that are mirrored by individuals in relationships). Thus, future research examining data from both singles and individuals in relationships would be beneficial for being able to make claims about the uniqueness or universality of our results.…”
Section: Discussionmentioning
confidence: 99%
“…Another variable that appears to be related to well‐being for singles is the extent to which they desire a romantic partner. In general, the desire to have something that one does not have is related to lower levels of well‐being (e.g., Hardin & Larsen, 2014; Larsen & McKibban, 2008; Park & MacDonald, in press). As Kislev (2021) has shown that reductions in desire for a partner over time are associated with increases in singles' life satisfaction, it would appear that assessments of singles' desire for a romantic partner may also be a useful indicator of overall well‐being.…”
Section: Introductionmentioning
confidence: 99%
“…This showed that partnered intercourse yields a more intense genital stimulation and possibly a more qualitative sexual experience than self‐stimulation. A recent paper indeed showed these same findings in a sample of over 500 men and women using an online survey assessing their perceived sexual pleasure in various sexual activities 37 . Multiple factors, including closeness to each other, building trust, feeling desired, and giving pleasure to a sexual partner have been put forward to play a role in women's partnered sexual contact 38 .…”
Section: Discussionmentioning
confidence: 67%
“…A recent paper indeed showed these same findings in a sample of over 500 men and women using an online survey assessing their perceived sexual pleasure in various sexual activities. 37 Multiple factors, including closeness to each other, building trust, feeling desired, and giving pleasure to a sexual partner have been put forward to play a role in women's partnered sexual contact. 38 Another study showed that men tend to defer to masturbation as a compensatory measure when partnered intercourse is not possible or not as often desired by the partner, suggesting that partnered intercourse is the preferred form of sexual contact.…”
Section: Discussionmentioning
confidence: 99%